1998
DOI: 10.1073/pnas.95.20.11763
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship of populations in China

Abstract: Despite the fact that the continuity of morphology of fossil specimens of modern humans found in China has repeatedly challenged the Out-of-Africa hypothesis, Chinese populations are underrepresented in genetic studies. Genetic profiles of 28 populations sampled in China supported the distinction between southern and northern populations, while the latter are biphyletic. Linguistic boundaries are often transgressed across language families studied, ref lecting substantial gene f low between populations. Nevert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
245
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(275 citation statements)
references
References 23 publications
27
245
2
1
Order By: Relevance
“…Northeast Asia is the major contributor to both Tibet (63.4%) and Tamang (59.7%) whereas Newar (44.7%) and Bhutan (41.1%) received equivalent percentages, followed by Kathmandu (22.3%). These results corroborate studies indicating a shared common ancestry between Tibet and the Northeast Asian collections of Japan and Korea by a variety of marker systems, including classical, 61,62 autosomal, 63 Y-chromosome 1,12,64,65 and mtDNA. 12,64,66,67 On the genetic origins of the Tibeto-Burman populations of the Himalayas T Gayden et al…”
Section: 0346supporting
confidence: 89%
“…Northeast Asia is the major contributor to both Tibet (63.4%) and Tamang (59.7%) whereas Newar (44.7%) and Bhutan (41.1%) received equivalent percentages, followed by Kathmandu (22.3%). These results corroborate studies indicating a shared common ancestry between Tibet and the Northeast Asian collections of Japan and Korea by a variety of marker systems, including classical, 61,62 autosomal, 63 Y-chromosome 1,12,64,65 and mtDNA. 12,64,66,67 On the genetic origins of the Tibeto-Burman populations of the Himalayas T Gayden et al…”
Section: 0346supporting
confidence: 89%
“…36 This study represents the largest number of founder event mutation profiles identified so far in Han populations. On the basis of the presumed population distribution and migration patterns of Han populations in East Asia as determined by population genetic studies 30 and the specific haplotypes of these founder mutations, we speculate that these common mutations in the PTS gene of East Asian individuals all originated from Han populations.…”
Section: Selection Of a Marker For Linkage Analysismentioning
confidence: 91%
“…29 Excluding the Filipinos, no significant difference in the allele frequency for D11S1347 was seen across the populations studied (P40.05 for all groups), although a distinction has been previously proposed for southern and northern populations in East Asia. 30 The founder events and mutations in East Asia To examine the possibility of founder event effects involving the PTS common mutations observed in East Asia, the haplotype of mutations in conjunction with D11S1347 alleles were evaluated by DNA analysis for samples where samples from the parents of probands were available. There were 43 (Table 2, Po0.01 for all groups).…”
Section: Selection Of a Marker For Linkage Analysismentioning
confidence: 99%
“…15 Moreover, the STR loci are especially valuable for the study of genetic relationships of closely related populations. [16][17][18][19] In this study, we applied the autosomal STR variation analysis to three population samples from Tibet to explore the peopling of the Himalayas.…”
Section: Introductionmentioning
confidence: 99%